Teachers’ perception towards early childhood literacy development methods in ‘aisyiyah bustanul athfal (ABA) kindergarten - Rany Maylani; Ega Asnatasia Maharani (Journal of Early Childhood Care and Education (JECCE), 2022)
The literacy ability of early childhood is inseparable from their teacher’s role in teaching literacy for children. The knowledge and methods used by the teacher are expected to be able to improve children's skills to comprehend the content of text and become active readers in the future. This research aims to find out teacher's perception towards early childhood literacy development methods in ‘Aisyiyah Bustanul Athfal (ABA) Kindergarten in Depok Sub-district. The research method employed in this research is qualitative descriptive. The sampling technique is purposive sampling in order to obtain 8 participants out of 4 kindergartens in Depok Sub-district.  The research data were analyzed by thematic analysis technique using NVivo 12 software. The findings revealed that: (1) teachers’ perception towards early childhood literacy development is mostly defined as the skill to reading and writing. (2) Teacher implementation on the early childhood literacy is carried out through activities involving printed learning media. (3) The development method for early childhood literacy learning is still limited to storytelling and writing. (4) School support for early childhood literacy development methods consists of providing facilities and infrastructures, and supporting teachers create published story books. However, the problems and obstacles faced by teachers are the lack of availability of reading books and inadequate infrastructure.